Water accounting international approaches to policy and decision-making - Godfrey, Jayne M.; Chalmers, Keryn; Edward Elgar Publishing (Cheltenham [England] : Edward Elgar Pub., 2012)
One of the most pressing global issues of the 21st century is the scarcity of water of a quantity appropriate to ensure economic, environmental and social sustainability. In addressing the issue through policy and management, of critical importance is access to high quality information. But water scarcity has many implications, and it is possible that different reporting approaches, generally called water accounting systems, can be appropriate to addressing them. In this groundbreaking book, international experts respond to the question: what role can water accounting play in resolving individual, organizational, industry, national and international economic, social and environmental issues? They explore how various forms of water accounting are utilized and the issues that they address.
pt. 1. Water accounting systems -- pt. 2. Application and evaluation of water accounting systems -- pt. 3. Contemporary issues addressed by water accounting.
Includes bibliographical references and index.
Keywords: Water-supply -- Accounting; Electronic books